2019
DOI: 10.1002/pds.4778
|View full text |Cite
|
Sign up to set email alerts
|

Classification and characteristics of on‐label and off‐label apixaban use in Denmark and Sweden

Abstract: Purpose: To estimate the proportion of apixaban users who received the drug for on-label indications and characterise the patients using apixaban for on-label and off-label indications. Methods:We report results from two independently conducted studies in Denmark and Sweden,with 19,709 Danish and 17,592 Swedish patients, who received at least one outpatient dispensing of apixaban as identified through nationwide prescription registries. Indications, inferred from inpatient and hospital diagnoses recorded at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Oral factor Xa and direct thrombin inhibitors have been approved for use and are associated with a reduction in the risk of stroke or systemic embolism (SSE) in patients with nonvalvular atrial fibrillation (AF) and venous thromboembolism. [5][6][7][8][9][10][11] Clinical use of these direct oral anticoagulants (DOACs) has been extended to off-label indications such as heparin-induced thrombocytopenia and antiphospholipid syndrome [12][13][14] ; however, the assumption of generalized interchangeability between DOACs and warfarin is potentially problematic. For example, dabigatran etexilate used for thromboprophylaxis of mechanical heart valves demonstrated higher rates of both ischemic stroke and bleeding.…”
mentioning
confidence: 99%
“…Oral factor Xa and direct thrombin inhibitors have been approved for use and are associated with a reduction in the risk of stroke or systemic embolism (SSE) in patients with nonvalvular atrial fibrillation (AF) and venous thromboembolism. [5][6][7][8][9][10][11] Clinical use of these direct oral anticoagulants (DOACs) has been extended to off-label indications such as heparin-induced thrombocytopenia and antiphospholipid syndrome [12][13][14] ; however, the assumption of generalized interchangeability between DOACs and warfarin is potentially problematic. For example, dabigatran etexilate used for thromboprophylaxis of mechanical heart valves demonstrated higher rates of both ischemic stroke and bleeding.…”
mentioning
confidence: 99%
“…Underdosing is more common than overdosing in real-world studies. The prevalence of underdosing in real-world studies ranges from 8% to 52% [ 38 ]. Underdosing of NOACs more commonly occurs in studies of Asian patients (20–50%) than in studies of non-Asian patients (8–20%).…”
Section: Real-world Evidence Of Underdosingmentioning
confidence: 99%
“… 2 4 Multiple studies have shown that DOACs are frequently used off-label and at incorrect doses. 5 , 6 Such practice places patients at risk for bleeding and thromboembolic events. 7 , 8 Inappropriate prescribing is likely a consequence of inadequate DOAC education, familiarity, and prescribing experience.…”
Section: Introductionmentioning
confidence: 99%